If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2z-2)-2(3-2z)=4
We simplify the equation to the form, which is simple to understand
2(2z-2)-2(3-2z)=4
Reorder the terms in parentheses
+(+4z-4)-2*(3-2z)=4
Remove unnecessary parentheses
+4z-4-2+*(+3-2z+)=+4
Reorder the terms in parentheses
+4z-4+(-6+4z)=4
Remove unnecessary parentheses
+4z-4-6+4z=+4
We move all terms containing z to the left and all other terms to the right.
+4z+4z=+4+4+6
We simplify left and right side of the equation.
+8z=+14
We divide both sides of the equation by 8 to get z.
z=1.75
| lnx+2x=0 | | 6x+39=16x-64 | | 4(2x-3)=10x-2(2x+3) | | x+42=5x | | 2x+19=4x-5 | | 179-7x=29x+15 | | 9-7x=33-14x | | 153-2x=43x+23 | | 2x+7=-89-10x | | 14-10x=124-45x | | 48=x(x+8) | | 7v^2-27v-4=0 | | 4x+37=14x-53 | | 5m^2+6m-8=0 | | x*25=50 | | 50x^2+50x-1000=0 | | .1x+x=125000 | | 2x+3(x-2)=4 | | 2y-5=15 | | (x-4)(x+5)=0 | | 1.1=4y+16.7 | | .40*55=x | | 5(x-3)=8-3x | | 6x^3-5x^2-4x+3= | | 6x^3-5x^2-4x+3byx-1= | | x^2-11x-9=0 | | x^2-4x+2=-2 | | 7x-3=12+2x | | 1(1x+12)= | | d-15=3d-3 | | 48-7d=-8+d | | 18d+1=17d+6 |